USING â€œDICTOGLOSâ€ TO ENLARGE SENIOR HIGH SCHOOL STUDENTSâ€™ ABILITY IN WRITING - Diah Paramita Sari; Safra Apriani Zahraa; Rionaldi - - (INOVISH JOURNAL, 2020)
Dictoglos can be used as a strategy in writing, it is expected that student can improve their writing. The aim of this study was to analyze the use of â€œDictoglosâ€ to enlarge senior high school studentsâ€™ ability in writing. This study was literature study research. The methods of collecting the primary data were documentation and observation. Meanwhile, journals, documentation books, and internet were taken for the secondary data. This study was analyzed using descriptive analysis method. Based on the data analyzed, it can be concluded that Dictoglos is an interesting and exciting strategy that can be applied in teaching writing. This strategy assists the students to reproduce and construct the component of the text. There are six steps in teaching a dictoglos; 1) Selecting a content-related to the text and read it aloud at a normal speaking. 2) Rereading the text twice more. 3) Having the students work in pairs to re-create as much of the text as possible using the note taken by each of the partners to write the text as closely as possible to the original text as read to the teacher. 4) Having two pairs to meet together and pool their re-create of the text to reconstruct it more completely. 5) Having the group of four works together to write down as much of the text as possible. 6) Asking one of each group to read the groups re-creation of the text and ask the other groups to see how closely it matches their version.